PENGARUH KOMPENSASI DAN DISIPLIN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN PADA BAGIAN REKAM MEDIS DI RUMAH SAKIT MATA CICENDO BANDUNG - NUNIEK DEWI PRAMANIK NUNIEK DEWI PRAMANIK (POLITEKNIK PIKSI GANESHA, 2019)
This study aims to determine how much influence compensation and work discipline on the performance of the employee of the medical record at Cicendo Eye Hospital Bandung. The research method used is descriptive analysis method and multiple linear regression analysis with quantitative approach. The data used in this study are primary and secondary data. Data collection techniques used questionnaires with ordinal scales and interviews. The sample in this study amounted to 30 employees with sampling technique saturation is the technique of determining the sample when all members of the population used as a sample or if the population is relatively small number or less than 100 people. The data is processed statistically using SPSS Version 21 for windows tool. In partial compensation effect of 37.4% on employee performance, and work discipline effect of 26.8% on employee performance. Simultaneously, compensation and work discipline contribute 64.2% to employee performance, while the rest of 35.8% is the influence of variabels that are not researched outside the study. The results of this study indicate that Compensation and Work Discipline have positive and significant impact on Employee Performance of medical record at Cicendo Eye Hospital Bandung.